Functional Evolution in the Plant SQUAMOSA-PROMOTER BINDING PROTEIN-LIKE (SPL) Gene Family - Preston, Jill C.; Hileman, Lena (Frontiers in Plant Science, 2013)
The SQUAMOSA-PROMOTER BINDING PROTEIN-LIKE (SPL) family of transcription factors is functionally diverse, controlling a number of fundamental aspects of plant growth and development, including vegetative phase change, flowering time, branching, and leaf initiation rate. In natural plant populations, variation in flowering time and shoot architecture have major consequences for fitness. Likewise, in crop species, variation in branching and developmental rate impact biomass and yield. Thus, studies aimed at dissecting how the various functions are partitioned among different SPL genes in diverse plant lineages are key to providing insight into the genetic basis of local adaptation and have already garnered attention by crop breeders. Here we use phylogenetic reconstruction to reveal nine major SPL gene lineages, each of which is described in terms of function and diversification. To assess evidence for ancestral and derived functions within each SPL gene lineage, we use ancestral character state reconstructions. Our analyses suggest an emerging pattern of sub-functionalization, neo-functionalization, and possible convergent evolution following both ancient and recent gene duplication. Based on these analyses we suggest future avenues of research that may prove fruitful for elucidating the importance of SPL gene evolution in plant growth and development.